Haematopoietic cell transplantation for blastic plasmacytoid dendritic cell neoplasm: a North American multicentre collaborative study. (4th October 2017) - Kharfan‐Dabaja, Mohamed A.; Al Malki, Monzr M.; Deotare, Uday; Raj, Renju V.; El‐Jurdi, Najla; Majhail, Navneet; Cherry, Mohamad A.; Bashir, Qaiser; Darrah, Justin; Nishihori, Taiga; Sibai, Hassan; Hamadani, Mehdi; et al.
Summary: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is incurable with conventional therapies. Limited retrospective data have shown durable remissions after haematopoietic cell transplantation (HCT) [allogeneic (allo) or autologous (auto)]. We conducted a multicentre retrospective study in BPDCN patients treated with allo‐HCT and auto‐HCT at 8 centres in the United States and Canada. Primary endpoint was overall survival (OS). The population consisted of 45 consecutive patients who received an allo‐HCT ( n  = 37) or an auto‐HCT ( n  = 8) regardless of age, pre‐transplant therapies, or remission status at transplantation. Allo‐HCT recipients were younger (50 (14–74) vs. 67 (45–72) years, P  = 0·01) and had 1‐year and 3‐year OS of 68% [95% confidence interval (CI) = 49–81%] and 58% (95% CI = 38–75%), respectively. Allo‐HCT in first complete remission (CR1) yielded superior 3‐year OS (versus not in CR1) [74% (95% CI = 48–89%) vs. 0, P  < 0·0001]. Allo‐HCT outcomes were not impacted by regimen intensity [3‐year OS for myeloablative conditioning = 61% (95% CI = 28–83%) vs. reduced‐intensity conditioning = 55% (95% CI = 28–76%)]. One‐year OS for auto‐HCT recipients was 11% (95% CI = 8–50%). These results demonstrate efficacy of allo‐HCT in BPDCN, especially in patients in CR1. Pertaining to auto‐HCT, our results suggest lack of efficacy against BPDCN, but this observation is limited by the small sample size. Larger prospective studies are needed to better define the role of HCT in BPDCN.